Organic Rankine Cycle for Energy Recovery System - De Pascale, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The rising trend in the global energy demand poses new challenges to humankind. The energy and mechanical engineering sectors are called to develop new and more environmentally friendly solutions to harvest residual energy from primary production processes. The Organic Rankine Cycle (ORC) is an emerging energy system for power production and waste heat recovery. In the near future, this technology can play an increasing role within the energy generation sectors and can help achieve the carbon footprint reduction targets of many industrial processes and human activities. This Special Issue focuses on selected research and application cases of ORC-based waste heat recovery solutions. Topics included in this publication cover the following aspects: performance modeling and optimization of ORC systems based on pure and zeotropic mixture working fluids; applications of waste heat recovery via ORC to gas turbines and reciprocating engines; optimal sizing and operation of ORC under combined heat and power and district heating application; the potential of ORC on board ships and related issues; life cycle analysis for biomass application; ORC integration with supercritical CO2 cycle; and the proper design of the main ORC components, including fluid dynamics issues. The current state of the art is considered and some cutting-edge ORC technology research activities are examined in this book.